Síntesis y estudio de propiedades de películas delgadas del compuesto CsXFA(1-X)PbI3 crecido con estructura perovskita para ser usadas como capa activa en celdas solares híbridas (2019)
In this project the properties of the thin films of the compound CsXFA(1-X)PbI3 grown with perovskite structure were studied in such a way that they can be used as an active layer in hybrid solar cells; for this, the appropriate synthesis conditions for the production of FAPbI3 films were first established from four factors: type of solvent, followed by annealing temperature next to the annealing time to finally study the concentration of lead iodide in the precursor solution. Subsequently, the effect of the substitution of the formamidinio ion when adding the cesium ion in the films of lead iodide and formamidinium was evaluated. From structural, morphological and optical characterizations made to the synthesized CsXFA (1-X) PbI3 films it was found that the addition of cesium in the films retarded the degradation of the black phase to the yellow phase of perovskite, furthermore it was determined that cesium concentrations 0≤X≤0.20 cesium ions are introduced into the crystal lattice effectively while for the value X = 0.30 a new phase of non-perovskite appears.